Ethnobotanical data needs and their application in biology learning - Marinda Sari Sofiyana; Dhamas Mega Amarlita; Pipit Mustika Ningrum (Universitas Islam Balitar, 2026)
Ethnobotanical knowledge plays an important role in connecting biological concepts with local wisdom and contextual learning; however, its integration into formal biology education remains limited. This study aims to analyze the needs for ethnobotanical data among secondary school students and biology education students, as well as to examine its current application in biology learning materials. A mixed-methods approach was employed, involving questionnaires, semi-structured interviews, and document analysis. Questionnaire data were collected from secondary school students and biology education students to identify priority ethnobotanical data categories, including local plant names, scientific names, plant parts used, traditional functions, cultural values, and conservation aspects. Interview data were used to explore perceptions of usefulness and preferred data presentation formats, while document analysis examined the extent of ethnobotanical integration in textbooks, learning modules, and curriculum documents. The results indicate that both groups expressed high to very high levels of need for ethnobotanical data, with biology education students consistently reporting higher needs, particularly for scientific and systematically organized information. Interview findings revealed that ethnobotanical data supported conceptual understanding, relevance to local contexts, teaching preparation, and research activities, with a strong preference for structured and visual presentation formats. Document analysis showed that existing biology learning materials provide limited, fragmented, and unsystematic ethnobotanical content with weak alignment to learning objectives. These findings highlight a significant gap between learners’ needs and available learning resources. The study implies the necessity of developing structured, contextual, and locally based ethnobotanical learning materials to enhance biology learning and support sustainable education.